The change of first metatarsal head articular surface position after Lapidus arthrodesis - Klouda, Jan (BMC Musculoskelet Disord, 2018)
BACKGROUND: The Lapidus procedure has been used for hallux valgus deformity correction since 1931. In some cases, the arthrodesis results in an unfavourable lateral inclination of first metatarsal head articular surface. The objective of our study was to evaluate the change of orientation of this articular surface in relation to the second metatarsal axis by comparing pre- and postoperative radiographs. The secondary target was to evaluate possible benefits of combination of Lapidus and Akin procedures in the reduction of hallux valgus deformity. METHODS: We evaluated 449 pre- and postoperative radiographs of 134 operations from 2010 to 2015. Routinely used angle measurements were performed on all X-rays. A sum of tangential angle to the second axis and distal articular set angle values was chosen as the best indicator for the deformity correction success. RESULTS: The mean value of these angles total was 5.2° ±9.3° before and 14.2° ±7.8° after the operation. In the group of patients, where the additional Akin osteotomy was used, the mean value was 5.3° ±8.4° before and 6.9° ±10.2° after the surgery. The mean difference in values between the two groups (with and without Akin procedure) was 7.3° of extra correction in favour of the group with the Akin osteotomy. CONCLUSIONS: The mean worsening of the tangential angle after Lapidus operation was 6.1° ±6.9°, which counts for significant deterioration after a surgery. The Akin osteotomy was found to be a valuable addition to the Lapidus arthrodesis, which improves the position of articular surfaces in first metatarsophalangeal joint.